'Techno-populism' as a new party family: the case of the Five Star Movement and Podemos. Issue 2 (4th May 2018) - Bickerton, Christopher J.; Accetti, Carlo Invernizzi
ABSTRACT: Democratic politics in Southern Europe have been shaken by the emergence of the Five Star Movement (M5S) in Italy and Podemos in Spain. Initially dismissed as protest movements, both point to broader structural transformations taking place within the region's political systems. Focusing on three dominant notions in the literature, 'anti-system', 'anti-establishment' and 'populist' party types, this article critically discusses each of these conceptual categories. It finds that none of them captures the originality of these movements, namely their combination of 'populist' and 'technocratic' conceptions of politics and modes of presentation. Revisiting the term 'techno-populism, ' this article recasts it as a new party family. As well as shedding light on the distinctive nature of the M5S and Podemos, this article aims to contribute to defining a broader 'ideal-type' of techno-populism, which can serve as the basis for a new research agenda combining work on technocracy, populism and political parties.